2021
DOI: 10.3390/molecules26082328
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Curcumin Loaded in Golden Pompano (Trachinotus blochii) Head Phospholipid and Soybean Lecithin Liposomes: Preparation, Characteristics and Anti-Inflammatory Properties

Abstract: In this study, we compared the characteristics and in vitro anti-inflammatory effects of two curcumin liposomes, prepared with golden pompano head phospholipids (GPL) and soybean lecithin (SPC). GPL liposomes (GPL-lipo) and SPC liposomes (SPC-lipo) loaded with curcumin (CUR) were prepared by thin film extrusion, and the differences in particle size, ζ-potential, morphology, and storage stability were investigated. The results show that GPL-lipo and SPC-lipo were monolayer liposomes with a relatively small part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Hasan et al demonstrated that the size of curcumin-nanoliposome composed of soy lecithin was 132 ± 1.3 nm, with a PDI value of 0.20 ± 0.01 [ 36 ]. Gao et al prepared liposome containing curcumin using soy lecithin and cholesterol as phospholipids, and the liposome exhibited a spherical shape with an average size of 157.97 ± 1.41 nm [ 37 ]. Similarly, Bonaccorso et al investigated curcumin-loaded solid lipid nanoparticles composed of a phospholipid, 2-Dimyristoyl-sn-glycero-3-phosphocholine, which had a size of 127.10 ± 11.30 nm.…”
Section: Discussionmentioning
confidence: 99%
“…Hasan et al demonstrated that the size of curcumin-nanoliposome composed of soy lecithin was 132 ± 1.3 nm, with a PDI value of 0.20 ± 0.01 [ 36 ]. Gao et al prepared liposome containing curcumin using soy lecithin and cholesterol as phospholipids, and the liposome exhibited a spherical shape with an average size of 157.97 ± 1.41 nm [ 37 ]. Similarly, Bonaccorso et al investigated curcumin-loaded solid lipid nanoparticles composed of a phospholipid, 2-Dimyristoyl-sn-glycero-3-phosphocholine, which had a size of 127.10 ± 11.30 nm.…”
Section: Discussionmentioning
confidence: 99%